Molecular mechanisms of programmed cell death in methamphetamine-induced neuronal damage - Guo, Dongming; Huang, Xinlei; Xiong, Tianqing; Wang, Xingyi; Zhang, Jingwen; Wang, Yingge; Liang, Jingyan (Frontiers in Pharmacology, 2022)
Methamphetamine, commonly referred to as METH, is a highly addictive psychostimulant and one of the most commonly misused drugs on the planet. Using METH continuously can increase your risk for drug addiction, along with other health complications like attention deficit disorder, memory loss, and cognitive decline. Neurotoxicity caused by METH is thought to play a significant role in the onset of these neurological complications. The molecular mechanisms responsible for METH-caused neuronal damage are discussed in this review. According to our analysis, METH is closely associated with programmed cell death (PCD) in the process that causes neuronal impairment, such as apoptosis, autophagy, necroptosis, pyroptosis, and ferroptosis. In reviewing this article, some insights are gained into how METH addiction is accompanied by cell death and may help to identify potential therapeutic targets for the neurological impairment caused by METH abuse.